Perspectives on the Genetic Associations of Ankylosing Spondylitis - Wordsworth, B. Paul; Cohen, Carla J.; Davidson, Connor; Vecellio, Matteo (Frontiers in Immunology, 2021)
Ankylosing spondylitis is a common cause of inflammatory arthritis of the spine that has a complex polygenic aetiology. Genome-wide association studies have identified more than 100 loci. These include some involved in antigen presentation by Class 1 major histocompatibility complex molecules (HLA-B27, ERAP1 & ERAP2), some in Th17 cells (IL6R, IL23R, TYK2 & STAT3), and others in macrophages and T-cells (IL7R, CSF2 & GPR65). The insights from these observations have helped the development of several potential new therapies targeting IL-17 and GM-CSF, for example. Many other associations lie outside the coding sequences of genes or in intergenic regions where their functional relationship to any particular gene is difficult to assess. Most genetic associations with AS likely reflect polymorphisms in parts of the genome concerned with cell type-specific regulation of gene expression. Understanding the mechanisms underlying these associations should help to reveal pathogenic pathways involved in AS and potential cellular and molecular targets for drug therapy. Polygenic risk scores (using known genetic associations with AS) can be effective for the diagnosis of AS, particularly when applied to patients with a relatively high pre-test probability of AS. Genetic prediction of disease outcomes and response to biologic therapies is not currently practicable.